2023
DOI: 10.3390/biomedicines11092465
|View full text |Cite
|
Sign up to set email alerts
|

Which Comes First, Nonalcoholic Fatty Liver Disease or Arterial Hypertension?

Julia A. Golubeva,
Anna F. Sheptulina,
Anastasia Yu. Elkina
et al.

Abstract: Non-alcoholic fatty liver disease (NAFLD) and arterial hypertension (AH) are widespread noncommunicable diseases in the global population. Since hypertension and NAFLD are diseases associated with metabolic syndrome, they are often comorbid. In fact, many contemporary published studies confirm the association of these diseases with each other, regardless of whether other metabolic factors, such as obesity, dyslipidemia, and type 2 diabetes mellites, are present. This narrative review considers the features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 182 publications
0
2
0
Order By: Relevance
“… 30 The underlying mechanism of the relationship between hypertension and MASLD might be insulin resistance, systemic inflammation, activation of the renin-angiotensin-aldosterone system and sympathetic nervous system, oxidative stress, gut microbiota disbalance, sex hormone, and genetic factors. 31 In hypertensive patients, the prevalence of hepatic steatosis exhibits a direct correlation with the severity of hypertension. 32 Additionally, a history of hypertension increases the risk of developing MASLD.…”
Section: Discussionmentioning
confidence: 99%
“… 30 The underlying mechanism of the relationship between hypertension and MASLD might be insulin resistance, systemic inflammation, activation of the renin-angiotensin-aldosterone system and sympathetic nervous system, oxidative stress, gut microbiota disbalance, sex hormone, and genetic factors. 31 In hypertensive patients, the prevalence of hepatic steatosis exhibits a direct correlation with the severity of hypertension. 32 Additionally, a history of hypertension increases the risk of developing MASLD.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension, with a global prevalence of 31.1% ( 10 ), is a key modifiable risk factor in NAFLD's development and progression ( 11 , 12 ). Recent meta-analyses have shown that the presence of hypertension significantly increased the risk of NAFLD events by 47% ( 13 ), and the latest evidence from Mendelian randomization analysis based on Genome-Wide Association Studies further indicated a causal relationship between hypertension and commonly measured blood pressure parameters SBP, DBP, and NAFLD ( 14 ).…”
Section: Introductionmentioning
confidence: 99%